Discovery of human TyrRS inhibitors by structure-based virtual screening, structural optimization, and bioassays. Issue 16 (22nd March 2019) - Huang, Shenzhen; Wang, Xiang; Lin, Guifeng; Cheng, Jie; Chen, Xiuli; Sun, Weining; Xiang, Rong; Yu, Yamei; Li, Linli; Yang, Shengyong
Abstract : A small molecule with potent activity diverts human Tyrosyl-tRNA synthetase (TyrRS) to the nucleus for protection against DNA damage. Abstract : The human tyrosyl transfer-RNA (tRNA) synthetase (TyrRS), which is well known for its essential aminoacylation function in protein synthesis, has been shown to translocate to the nucleus and protect against DNA damage caused by external stimuli. Small molecules that can fit into the active site pocket of TyrRS are thought to affect the nuclear role. The exploitation of TyrRS inhibitors has attracted attention recently. In this investigation, we adopted a structure-based virtual screening strategy and subsequent structure–activity relationship analysis to discover new TyrRS inhibitors, and identified a potent compound 5, 7-dihydroxy-6, 8-bis((3-hydroxyphenyl)thio)-2-phenyl-4 H -chromen-4-one (compound11, K i = 8.8 μM). In intact HeLa cells, this compound showed a protective effect against DNA damage. Compound11 is a good lead compound for the further development of drugs against disorders caused by DNA damage.